Musculoskeletal Injuries in Ultra-Endurance Running: A Scoping Review - Scheer, Volker; Krabak, Brian J. (Frontiers in Physiology, 2021)
Ultra-endurance running (UER) has seen an important increase in participation over the last few decades. Long hours of UER can lead to excessive stress on the body, resulting in musculoskeletal injuries (MSKI). UER is not a uniform sport and events can differ considerably in distance (over 42.195 km), time (e.g., events over 6 hours) and multi-day or multi-stage events on various surfaces (e.g., track, on-road, off-road). The aim of this review is to examine MSKI in UER providing an overview the most common injuries by anatomical regions, specific diagnosis during competitions and training for different UER distances and terrain. Our electronic literature search (PubMed, SPORTDiscus, Web of Science) identified a total of 13 studies (9 in competition, and 4 in training). Anatomical site, diagnosis and rate of injuries differ between competition and training as well as between different UER types. MSKI are observed in 18% of multi-stage events (0.7-1.8 injuries / runner and 7.2 injuries/ 1000 h). Most MSKI involve the lower leg (35.0%), ankle (16.8%), knee (13.1%) and foot (12.6%), with main diagnosis of medial tibial stress syndrome (30.1%) and patella femoral pain syndrome (PFPS; 7.2%). Single, continuous UER events differ between a 1005 km road race with almost all of the injuries due to overuse, with the main anatomical site of the knee (31%), ankle (28%) and lower leg (14%) and main diagnosis of PFPS (15.6%), compared to a 65 km trail race, with 32.8% of MSKI, mainly on the foot (plantar fasciitis (28.6%)), ankle (sprain (28.6%)) and knee. Timed-UER events (injury rate of 2.1 injuries/ athlete) observed most injuries on the ankle (36%) and knee (19%), with the main diagnosis of tendinitis of the foot dorsiflexors (30%). Injuries during training most commonly affect, the back (42%), and knee (40%) and bone stress injuries (22%). Main diagnoses include ankle sprain (18%), iliotibial band injury (16%) and Achilles tendinopathy (11%). Future considerations include examining MSKI in different UER events, environments and surfaces, and on larger study populations. Establishing risk factors, examining sex differences and using a standard reporting system of MSKI in UER are also important.